Drainage Systems for Flatwoods Citrus in Florida - Brian Boman; Dave Tucker (EDIS)
This is Document No. CH165 and Circular 1412, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002.